1974
DOI: 10.1136/jcp.27.2.140
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of serum acid and alkaline phosphatase determinations in prostatic cancer with a clinical validation of an acid phosphatase assay utilizing adenosine 3′ -monophosphate as substrate

Abstract: SYNOPSIS Serum acid phosphatase (AcPase) was measured by a colorimetric method utilizing adenosine 3'-monophosphate as substrate in 389 patients. In about half the cases blood was taken shortly after a rectal examination. The upper reference limit (mean + 2SD) for 116 cases with miscellaneous illness after eliminating outliers was 4f1 International Units per litre (U/I) at 37°C, and no correlation existed between AcPase activity and age in these subjects (r = 0 040). Eight of 18 patients with untreated carcino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1976
1976
1999
1999

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…TAP has also been widely used in the study of development and progression of bone metastases in prostate cancer, with a sensitivity between 60 and 85% [15,16]. Among our group of patients, only one patient of group (BPHzIzII) presented high levels of TAP, and this was the patient with associated hepatitis.…”
Section: Discussionmentioning
confidence: 88%
“…TAP has also been widely used in the study of development and progression of bone metastases in prostate cancer, with a sensitivity between 60 and 85% [15,16]. Among our group of patients, only one patient of group (BPHzIzII) presented high levels of TAP, and this was the patient with associated hepatitis.…”
Section: Discussionmentioning
confidence: 88%
“…Various studies have shown the effectiveness of total alkaline phosphatase (TAP), as it is found to be elevated in 60-85% of CaP patients with bone metastases [2,3]. However, TAP measures the activity of several isoforms, mainly the bone-and liver-specific isoenpT1-3N0M0…”
Section: Introductionmentioning
confidence: 99%